On the spectral radius of bipartite graphs - Fan, Dandan; Wang, Guoping; Zao, Yuying (Utilitas Mathematica, 2020)
The adjacency matrix A(G) of a graph G is the n x n matrix with its (t,j)-entry equal to 1 if Vi and Vj are adjacent, and 0 otherwise. The spectral radius of G is the largest eigenvalue of A(G). In this paper we determine the graph with maximum spectral radius among all connected bipartite graphs of order n with a given matching number and a given vertex connectivity, respectively. © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.